Combined Heat and Power: Equipment Options and Application Alternatives - Bloomquist, R. Gordon (Distributed Generation & Alternative Energy Journal, 2002)
Combined heat and power (CHP) is the generation of electrical power, mechanical energy, and thermal energy. By fully using the energy available, fuel use efficiency can exceed 80 percent while air pollutant emissions are significantly decreased. Applications include all forms of industrial processes, commercial and institutional complexes, and single commercial and residential buildings. Generation equipment includes internal combustion engines, combustion turbines, steam turbines, Stirling engines, and fuel cells. Thermal energy is captured through the use of a heat recovery steam generation or, in the case of a steam turbine, is extracted at various temperatures and pressures. The thermal energy can be used directly in industrial processes or used for space heating, e.g., district heating. The thermal energy can also be used for cooling. Extracted or generated steam can be used in a steam-driven chiller, absorption, adsorption, or a desiccant system. Storage has also become an important component of many CHP systems and provides increased reliability to both electrical and thermal systems.